PEMANFAATAN MEDIA SOSIAL DALAM MANAJEMEN HUBUNGAN MASYARAKAT UNTUK MEMBANGUN BRAND AWARENESS PERGURUAN TINGGI - Rawis, Joulanda A. M.; Sumual, Shelty D. M.; Lengkong, Anthonio B.; Wuisan, Deiby D.; Siahaan, Waldemar (Jurnal Manajemen Pendidikan, 2025)
Brand awareness is not only measured by logo recognition, but also by the qualitative associations formed in the minds of stakeholders regarding the academic image, research quality, and social value offered by the institution. Objective: This study aims to examine the use of social media in Higher Education Public Relations (PR) management to build brand awareness. Methods: The study employs a Systematic Literature Review (SLR) design of publications from 2015–2024 retrieved from Scopus, Web of Science, Google Scholar, and DOAJ. Data were analyzed using Thematic Content Analysis to identify strategies, impacts, and challenges. Results: Social media has been shown to enhance institutional visibility, brand identity, and public engagement. Platforms such as Instagram, Twitter/X, LinkedIn, and YouTube contribute differently to dimensions of brand awareness, including recognition, recall, and top-of-mind awareness. However, challenges arise in content management, digital crisis response, misinformation, and measurement limitations. Novelty: This study proposes the Smart PR-Equity Model, an integrated framework combining symmetrical communication, multiplatform strategies, and digital brand equity indicators to strengthen higher education institutional reputation sustainably.